Cygnaeuksen jäljillä käsityönopetuksesta teknologiseen kasvatukseen - Kantola, Jouko (1997)
This study examines the development that has taken place in the teaching of handicraft in Finland from 1863 up till today, and also examining related future visions. The focus is mainly on the Department of Teacher Education in Jyväskylä, where - thanks to Cygnaeus - the teaching of handicraft was first started. The present study seeks to explore how the teaching of handicraft is shifting towards technological education in line with contemporary societal changes. The data were collected through essays, interviews, computer-assisted questionnaires, diaries, and ordinary questionnaires. A major part of the data was gathered by means of two separate questionnaires administered to all university departments training primary school teachers in Finland. The respondents were the same for both the questionnaires. The first questionnaire provided information about the realization of the curricula in the various teacher education departments. The second one dealt with the position of environmental education in the teaching of lecturers of Didactics for Technical work as well as with their attitudes to and awareness of environmental matters. Economic development and related technological expansion have led to environmental problems. A central task of pedagogy in the field of technology is to provide the students with the necessary skills and knowledge to remove these problems. Integration of technological and environmental education has been seen as one way to bridge the gap between these two theme areas. The present study does not, however, suggest that such integration should mean a full merger between technological and environmental education. In the Finnish teacher training institutes handicraft curricula based on the report by the 1912 Soininen Committee were followed to some extent up till the 1970s. The official goals set for handicraft are now about the same as they were at the tum of the 1970s. The emphasis lies on productive activities. Yet, the lecturers have, on their own initiative, introduced technological elements into the syllabi for technical work. In Jyväskylä, Oulu, Kajaani, and Savonlinna, at least, technology education has gained emphasis. Environmental elements have been discernible in syllabi ever since the 1970s. These elements have been introduced under various headings, such as health and safety at work, industrial hygiene, and purchase of raw materials. A major problem has been that the dangerous nature of some of the substances handled in handicraft classes has not been realized early enough. Work safety norms in handicraft have been established only as required by new regulations. The term "environmental education" does not occur as such in the curricula for handicraft in teacher training departments. In handicraft the teacher trainees are exposed to environment-related aspects, however, as mediated by their lecturers in technical work. The lecturers have brought up themes that develop their students' environmental awareness and sensitivity, e.g., issues pertaining to loading the environment and to its condition. The lecturers are fairly well aware of environmental matters, they know the terminology and also the qualities of the substances used in technical work. Most of them have replaced environmentally harmful substances with more friendly ones. The results of this study show that there are still evident needs for gearing the teaching of handicraft more closely to technological education. When constructing a curriculum of a new kind which calls for broader-based skills, both the natural and man-made environment, as well as the social environment, must be taken into account simultaneously. Conflicts between human activities and their various surroundings embedded within the culture and environment as a whole can be reduced by means of schooling and education. Teacher education should include technological education, encompassing the principle of sustainable development. Technological literacy, "technological awareness", becomes essential. Technological education needs environmental education as a counterbalance. In this regard, correctly-understood technological education and the increased importance of environmental education provide a sound basis for an integrated technological-environmental curriculum for teacher education.